2020
DOI: 10.3171/2020.5.jns201107
|View full text |Cite
|
Sign up to set email alerts
|

Endarterectomy for symptomatic internal carotid artery web

Abstract: OBJECTIVEThe carotid web (CW) is an underrecognized source of cryptogenic, embolic stroke in patients younger than 55 years of age, with up to 37% of these patients found to have CW on angiography. Currently, there are little data detailing the best treatment practices to reduce the risk of recurrent stroke in these patients. The authors describe their institutional surgical experience with patients treated via carotid endarterectomy (CEA) for a symptomatic internal carotid artery web.METHODSA retrospective, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In most publications, CW was defined as a shelf-like septum in the posterior wall of the carotid bulb. 1, 2, 4, 5, 7, 9-11, 13, 1619, 23-28 On the other hand, the greater development and thickness of the intima and the greater amount of elastic fibers in carotid vessel are probably linked to the presence of a higher frequency of CW on the carotid artery. 29 The mean length of symptomatic CW was relatively longer than asymptomatic CW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most publications, CW was defined as a shelf-like septum in the posterior wall of the carotid bulb. 1, 2, 4, 5, 7, 9-11, 13, 1619, 23-28 On the other hand, the greater development and thickness of the intima and the greater amount of elastic fibers in carotid vessel are probably linked to the presence of a higher frequency of CW on the carotid artery. 29 The mean length of symptomatic CW was relatively longer than asymptomatic CW.…”
Section: Resultsmentioning
confidence: 99%
“…3,4,16,18 The prevalence of symptomatic CW in patients who were operated on for a carotid stenosis varies from 3.0 to 15.6%. 7,19 After our literature review, the prevalence of symptomatic CW was 1.2% in patients with transient ischemic attack/stroke, 6.4% in patients with cryptogenic ischemic stroke, 1.1% in patients with large vessel occlusion stroke, and 4.4% in patients who operated on for carotid stenosis. Similar to the systematic review published by Zhang et al in 2018, 20 our study found that patients with CW were relatively young, with a higher prevalence of women.…”
Section: Discussionmentioning
confidence: 96%
“…In several studies, pathological examinations revealed that a CaW is a subtype of fibromuscular dysplasia. 1 , 2 , 14 , 15 ) A typical characteristic of CaW is intimal fibrous hyperplasia with minimal medial degeneration, 2 , 16 ) sometimes containing fibroelastic tissue with muscular tissue 17 ) and fibroelastic tissue with areas of myxoid degeneration. 18 ) In our case, the CaW showed different developmental phases with new intimal hyperplasia overlying the CaW distally.…”
Section: Discussionmentioning
confidence: 99%
“…CAS is the preferred treatment strategy because of its safety and effectiveness ( 43 ). Moreover, it has fewer perioperative complications ( 44 ). In this study, medical management, CAS, and CEA were used.…”
Section: Discussionmentioning
confidence: 99%